"You cannot contradict the engineer": Disencounters of modern technology, climate change, and power in the Peruvian Andes. (December 2019) - Stensrud, Astrid B
In the World Bank funded development program PSI Sierra, which aims to modernize irrigation technologies in the Peruvian highlands, the complexity of climate change is reduced to the manageable issues of water scarcity and lack of modern technology. By focusing on the encounters between farmers in Colca Valley and PSI engineers, the author argues that most of these encounters can best be analyzed as failed encounters or "disencounters", which confirm diverging interests and exacerbate differences. The article discusses three modes of disencounters: (a) diverging definitions of problems; (b) different technological practices in terms of flexibility, and (c) distrust emerging from an embodied history of structural inequality. The author argues that instead of supporting farmers to deal with their own-defined problems, the program—through these disencounters—produces other effects: (a) increased uncertainty; (b) the reproduction of hierarchies, and (c) the de-politicization of climate change, inequality, and poverty.